Cong Rock 17: A Social Fact of Keroncong Music in Semarang - Abdul Rachman; Udi Utomo; Zahrotul Fauziah (International Conference on Science, Education, and Technology, 2022)
Cong Rock 17 is a creative keroncong group in Semarang city. The phenomenon of Cong Rock 17 is captured as a social fact that is currently happening to keroncong in Semarang. This study aims to discover how the phenomenon of a social fact of Cong Rock 17 in keroncong music in Semarang. This study uses a qualitative approach. Data collection techniques include observation, interviews, field notes, and documentation. Data was checked using the validity method of triangulation data with sources. Data analysis was carried out using interactive data analysis, which was divided into three stages, including data collection, data reduction, data presentation, and concluding/verification. The research results show that the Cong Rock 17 social fact paradigm is based on two crucial issues: social structure and social institution. The social structure of Cong Rock 17 is that there are interactions and relationships between individuals and social positions in the Cong Rock 17. Each social position/role in Rock 17 carries out its respective main tasks and functions with a complete sense of responsibility for group solidity. While the social institution is the value ​​and norm held by the Cong Rock 17 members, which form the basis for attitudes and behaviour for the progress of the group, including routine training, discipline, loyalty, Ngemis (Ngopi Kemis), and ngibadah musik. This study concludes that the Cong Rock 17 Social Fact Paradigm from the aspects of the Social Structure and Social Institution keeps the Keroncong Orchestra solid, and sustained, and Semarang citizens always await its presence.